Efektivitas Media Miniatur Sumber Energi Listrik (MISEL)untuk Meningkatkan Hasil Belajar IPAS Kelas lll - Alya Oktaviana; Iis Daniati Fatimah (Paedagogie, 2026)
The lack of conceptual clarity among students about electrical energy sources is a direct result of the continued dominance of the lecture technique and textbooks in the classroom, which in turn leads to students' poor grasp of the subject. The purpose of this research was to design and test the Miniature of Electrical Energy Sources (MISEL) as a teaching tool for third graders at UPT SD Negeri Prantaan in order to establish its efficacy, validity, and practicability in the classroom. Researchers used the R&D approach in this investigation. Twelve third graders, six of whom were male and six of whom were female, served as the research subjects. Information was gathered by means of examinations, surveys, and records. Pre- and post-test results, teacher and student surveys, and validation from experts in the fields of material, media, and language provided the data. The N-Gain test and descriptive quantitative analysis were used to analyze the data. Based on the results, the MISEL media received a very valid score of 94% for material validation, a media validation score of 93%, and a valid score of 66% for language validation. Both the teachers' and students' responses were deemed very practical, with a practicality test percentage of 96% and 92.22%, respectively. According to the efficacy test, the average score went up from 75 on the pretest to 85 on the posttest. The average result from the N-Gain analysis was 0.70, which is considered high. Based on these findings, the Miniature of Electrical Energy Sources (MISEL) learning media is considered valid, practical, and effective for use in elementary school science and social studies (IPAS) learning, particularly on the topic of electrical energy sources for third-grade students.